2010
DOI: 10.1021/ef100617p
|View full text |Cite
|
Sign up to set email alerts
|

Study of Asphaltene and Metal Upgrading in the Vapor Extraction (VAPEX) Process

Abstract: The effect of the vapor dew point and matrix permeability on the movement of deposited streaks in the vapor extraction (VAPEX) process was investigated. Furthermore, the distribution of residual hydrocarbons, asphaltenes, resins, and metal chelate in the VAPEX cell was determined. Finally, the pattern of viscosity distribution in the VAPAX cell was calculated using a Computer Modelling Group (CMG) simulator. The experiments were conducted in sand packed on the Iranian bitumen by propane solvent. Asphaltene, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although the peaks around 1690 cm –1 because of the polar carbonyl and amide carbonyl groups were observed in all fractions, the absorbance was obviously much stronger in asphaltenes and resins than in aromatics and saturates, which indicated that the number of the polar groups were ranked as follows: asphaltenes > resins > aromatics and saturates. A similar characterization of functional groups in bitumen from Athabasca oil sands was reported by Yoon et al and Moschopedis et al Additionally, the existence of the multivalent metal ions could also enhance the polarity (the polarity refers to a separation of electric charge, which leads to an electric dipole or multipole moment of a molecule or its chemical groups; generally, polar molecules interact through dipole–dipole intermolecular forces and hydrogen bonds) of asphaltenes, , which will be detailed in the Elemental Analysis (EA) section. Previous simulation results by Murgich et al showed that the interaction force in asphaltene–asphaltene was larger than that in asphaltene–resin or resin–resin, which could be understood by the existence and number of polar groups in the molecules.…”
Section: Resultsmentioning
confidence: 57%
“…Although the peaks around 1690 cm –1 because of the polar carbonyl and amide carbonyl groups were observed in all fractions, the absorbance was obviously much stronger in asphaltenes and resins than in aromatics and saturates, which indicated that the number of the polar groups were ranked as follows: asphaltenes > resins > aromatics and saturates. A similar characterization of functional groups in bitumen from Athabasca oil sands was reported by Yoon et al and Moschopedis et al Additionally, the existence of the multivalent metal ions could also enhance the polarity (the polarity refers to a separation of electric charge, which leads to an electric dipole or multipole moment of a molecule or its chemical groups; generally, polar molecules interact through dipole–dipole intermolecular forces and hydrogen bonds) of asphaltenes, , which will be detailed in the Elemental Analysis (EA) section. Previous simulation results by Murgich et al showed that the interaction force in asphaltene–asphaltene was larger than that in asphaltene–resin or resin–resin, which could be understood by the existence and number of polar groups in the molecules.…”
Section: Resultsmentioning
confidence: 57%
“…For example, asphaltenes may be regarded as solids dissolved within the crude oil or even as solids dispersed in the bulk oil. ,,, Asphaltenes are mainly considered to be organic deposits. Elemental composition analyses also reveal some sulfur atoms, slightly lesser amounts of oxygen and nitrogen atoms, and often trace amounts of mainly vanadium and nickel atoms. , In addition, the asphaltene fraction is usually of higher molecular weight, (higher) polarity, and/or higher aromatic content compared to the remaining oil fractions . There is some disagreement regarding whether asphaltene precipitation is a reversible process (thermodynamic theory) or an irreversible process (colloidal theory).…”
Section: Introductionmentioning
confidence: 99%
“…Saniere et al illustrated that from the available heavy oil only a fraction is extracted by conventional methods [1]. Figure 1 shows the worldwide heavy oil resources and production.…”
Section: Introduction the Importance Of The Vapex Processmentioning
confidence: 99%